1996
DOI: 10.1056/nejm199610103351505
|View full text |Cite
|
Sign up to set email alerts
|

A Familial Syndrome of Hypocalcemia with Hypercalciuria Due to Mutations in the Calcium-Sensing Receptor

Abstract: Gain-of-function mutations in the calcium-sensing receptor are associated with a familial syndrome of hypocalcemia with hypercalciuria that needs to be distinguished from hypoparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
450
2
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(471 citation statements)
references
References 33 publications
12
450
2
4
Order By: Relevance
“…The calcium-sensing receptor can also activate phospholipase A2 to produce arachidonic acid, the metabolites of which, including 20-HETE, inhibit NKCC2 and ROMK. In support of this mechanism, Pearce et al have found six kindreds with an autosomal dominant inheritance of hypocalcemia and hypercalciuria who proved to have activating mutations in the calcium-sensing receptor (111,112). Vezzoli et al (113) examined four single-nucleotide polymorphisms (SNP) in exon 7 of the calcium-sensing receptor and found one SNP associated with a 13-fold higher risk of hypercalciuria.…”
Section: Dent Disease (X-linked Recessive Nephrolithiasis) Dent and mentioning
confidence: 99%
“…The calcium-sensing receptor can also activate phospholipase A2 to produce arachidonic acid, the metabolites of which, including 20-HETE, inhibit NKCC2 and ROMK. In support of this mechanism, Pearce et al have found six kindreds with an autosomal dominant inheritance of hypocalcemia and hypercalciuria who proved to have activating mutations in the calcium-sensing receptor (111,112). Vezzoli et al (113) examined four single-nucleotide polymorphisms (SNP) in exon 7 of the calcium-sensing receptor and found one SNP associated with a 13-fold higher risk of hypercalciuria.…”
Section: Dent Disease (X-linked Recessive Nephrolithiasis) Dent and mentioning
confidence: 99%
“…(1–3) The CaSR is a guanine‐nucleotide binding protein (G‐protein)‐coupled receptor (GPCR) that plays a pivotal role in Ca 2+ o homeostasis by transducing increases in the prevailing Ca 2+ o concentration into multiple signaling cascades that include G q/11 ‐protein–mediated activation of phospholipase C (PLC), which in the parathyroid glands and kidneys induces rapid increases in intracellular calcium (Ca 2+ i ) that lead to decreased parathyroid hormone (PTH) secretion and increased urinary calcium excretion, respectively 2, 4, 5. ADH is a genetically heterogeneous disorder most commonly caused by germline gain‐of‐function mutations of the CaSR, which is encoded by the CASR gene on chromosome 3q21.1, and this is referred to as ADH type 1 (ADH1; OMIM #601198) 1, 2, 5. However, some ADH patients and families have recently been shown to harbor germline mutations of G‐protein subunit‐α11 (Gα 11 ), which is encoded by the GNA11 gene (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…ADH1 patients have calcitropic phenotypes, such as hypocalcemia with inappropriately low or normal PTH concentrations and a relative hypercalciuria that is characterized by urinary calcium to creatinine ratios that are within or above the reference range,1, 8, 9 and mice with a gain‐of‐function CaSR mutation, that are representative of ADH1, have been reported to also have non‐calcitropic phenotypes such as cataracts 10. Although these features are similar to hypoparathyroidism, ADH1 is considered to represent a distinct disease entity from hypoparathyroidism, because affected individuals generally have PTH concentrations that are detectable and within the reference range 1, 8. Furthermore, ADH1 patients may also develop a Bartter‐like syndrome characterized by hypokalemic alkalosis, renal salt wasting, and hyperreninemic hyperaldosteronism,11, 12 and the use of active vitamin D metabolites to treat symptomatic ADH1 patients may result in the development of marked hypercalciuria, nephrocalcinosis, nephrolithiasis, and renal impairment 1, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic forms of HP are rare and usually associated with mutations in four genes: calcium‐sensing receptor ( CASR ) (Bai et al 1996; Pearce et al 1996; Watanabe et al 1998), glial cells missing homolog 2 ( GCM2 ) (Ding et al 2001), guanine nucleotide‐binding protein alpha‐11 ( GNA11 ) (Mannstadt et al 2013), and PTH itself (Arnold et al 1990; Parkinson & Thakker 1992; Sunthornthepvarakul et al 1999). …”
mentioning
confidence: 99%